Effects of rainfall intensities and slope gradients on nitrogen loss at the seedling stage of maize (Zea mays L.) in the purple soil regions of China - He, Shuqin; Gong, Yuanbo; Zheng, Zicheng; Luo, Ziteng; Tan, Bo; Zhang, Yunqi (International Journal of Agricultural and Biological Engineering, 2022)
Loss of soil nitrogen has been reported to reduce soil productivity and result in eutrophication. The objective of this work was to understand the mechanisms of nitrogen loss at the maize seedling stage from purple soil in the sloping farmlands of southwest China. The characteristics of nitrogen loss were explored in experiments simulating rainfall conditions during the maize seedling stage at different rainfall intensities (60 mm/h, 90 mm/h, and 120 mm/h) and slope gradients (10°, 15°, and 20°). The results showed that the runoff and sediment yield increased with time. The surface runoff and sediment yield increased with the rainfall intensity and slope gradient. Nitrogen losses increased in the surface runoff and sediment but decreased in the interflow as the rainfall intensity and slope gradient increased. Dissolved total nitrogen (DTN) was the main form of nitrogen in the surface runoff and interflow, and nitrate nitrogen (NO3-N) was the main form of DTN. The surface runoff and sediment accounted for less than half of the TN losses. Thus, interflow was the main pathway for nitrogen loss. The regression lines between the surface runoff and forms of nitrogen losses in the runoff and interflow were linear. The results indicated that an increasing rainfall intensity and slope gradient generally increased the surface runoff, sediment, and their nitrogen losses. However, the opposite trend was observed for the interflow and its nitrogen losses. Keywords: forms of nitrogen, surface runoff, interflow, sediment yield, slope gradient, rainfall intensity DOI: 10.25165/j.ijabe.20221502.6015 Citation: He S Q, Gong Y B, Zheng Z H, Luo Z T, Tan B, Zhang Y Q. Effects of rainfall intensities and slope gradients on nitrogen loss at the seedling stage of maize (Zea mays L.) in the purple soil regions of China. Int J Agric & Biol Eng, 2022; 15(2): 142–148.